Conservation Efforts of Wildlife Habitats Through the Formulation of Local Regulations on Biodiversity Conservation Management Areas - Lita Tyesta Addy Listya Wardhani; Amalia Diamantina; Luthfi Hafidz Rafsanjani (AMCA Journal of Community Development, 2025)
The protection and management of the environment as the primary life support system for humans in a harmonious, balanced manner through the preservation of biodiversity habitats within biodiversity conservation frameworks are manifestations of safeguarding the fundamental rights of every citizen, which must be continuously protected and ensured for its sustainability. This research aims to understand, analyze, and evaluate the implementation of biodiversity habitat preservation efforts through biodiversity conservation management areas through the enactment of regional legislation, including in the Province of Bangka Belitung Islands, Indonesia. This study utilizes a normative juridical legal research method with statute, case, conceptual, and analytical approaches. Data collection techniques involve literature review, observational methods, and in-depth interviews. This research findings indicate that the regulation regarding biodiversity conservation management has not yet been fully effective, as it primarily focuses on protection and lacks consideration for sustainable utilization. Challenges in biodiversity habitat preservation implementation include synchronization and harmonization issues in regulation, particularly regarding the division of authority between the central and regional governments in natural resource conservation and the limited involvement of communities, including local communities in conservation areas, to access and oversee the sustainable use of biodiversity resources based on local wisdom. Strengthening implementation measures, such as more robust and effective law enforcement, clear delineation of authority among institutional frameworks, and further development of substantive materials through scientific approaches in the field of biodiversity, is essential. Additionally, expanding the involvement of local communities in management and utilization activities in accordance with principles and procedures is necessary.